2014
DOI: 10.1016/j.bbamem.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Implicit membrane treatment of buried charged groups: Application to peptide translocation across lipid bilayers

Abstract: The energetic cost of burying charged groups in the hydrophobic core of lipid bilayers has been controversial, with simulations giving higher estimates than certain experiments. Implicit membrane approaches are usually deemed too simplistic for this problem. Here we challenge this view. The free energy of transfer of amino acid side chains from water to the membrane center predicted by IMM1 is reasonably close to all-atom free energy calculations. The shape of the free energy profile, however, for the charged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 95 publications
3
24
0
1
Order By: Relevance
“…Membrane incorporation proceeds by first inserting the N-terminal, followed by partially solvated basic amino acids ( Figure 7A), while C-terminal carboxylates in metabolites 1a and 3 remain exposed to the solvent. This agrees with previously described mechanisms for basic peptide penetration [30], and is putatively caused by a higher energetic cost to dehydrate C-terminal moieties [31]. In contrast, CIGB-552 and metabolite 5 maintain the looped conformation in the membrane environment.…”
Section: Simulations Of Cigb-552 and Its Derived Metabolitessupporting
confidence: 91%
See 1 more Smart Citation
“…Membrane incorporation proceeds by first inserting the N-terminal, followed by partially solvated basic amino acids ( Figure 7A), while C-terminal carboxylates in metabolites 1a and 3 remain exposed to the solvent. This agrees with previously described mechanisms for basic peptide penetration [30], and is putatively caused by a higher energetic cost to dehydrate C-terminal moieties [31]. In contrast, CIGB-552 and metabolite 5 maintain the looped conformation in the membrane environment.…”
Section: Simulations Of Cigb-552 and Its Derived Metabolitessupporting
confidence: 91%
“…However, we observed that the presence of aromatic residues only present at the C‐termini of CIGB‐552 and metabolite 5 translates in the formation of a hydrophobic cluster that ultimately results in a looped structure stabilized by the formation of a stiff salt bridge between an arginine and the COO − moiety. Although the maximum affordable time scale of the simulations differs significantly from experimental times, this structural organization could help internalization by reducing the free energy needed to translocate the C‐terminal carboxylate . Moreover, the looped conformation conserved in the two longest peptides offers a putative explanation for the similar characteristics displayed in contrast with metabolites 1 and 3a in terms of enhanced membrane interaction, internalization, and cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid and peptide translocation are useful in modeling the mechanism of peptide and of protein insertion to membranes 5 . Arginine was studied most extensively due to its significant role in Cell Permeating Peptides (CPP).…”
Section: Introductionmentioning
confidence: 99%
“…The solvation parameters of all atoms now depend on the position along the membrane normal and are modeled as a linear combination of the values corresponding to water and cyclohexane. [190] IMM1 has been applied to the modeling of fusion peptide assemblies, [191] computation of potentials of mean force for peptides in membranes, [192] presenilin, [193] rhodopsin, [194] the transmembrane dimer of amyloid precursor protein, [195] transmembrane structures of amyloid oligomers, [196] dimerization of the lutropin receptor, [197] gating of MscL, [198] the translocon, [199] peptide translocation through bilayers, [200] and others. In addition, the distance-dependent dielectric is modified to account for strengthening of the electrostatic interactions in the membrane.…”
Section: Heterogeneous Solventsmentioning
confidence: 99%
“…[188] The surface, transmembrane and dipole potentials are accounted for by a term of the form P i yðz i Þ q i , in which q i is the partial charge of atom i and y is the potential, obtained by GouyÀChapman theory, [183] explicit simulations, [187] analytical solutions to the PB equation, [189] or numerical solutions to the PB equation. [190] IMM1 has been applied to the modeling of fusion peptide assemblies, [191] computation of potentials of mean force for peptides in membranes, [192] presenilin, [193] rhodopsin, [194] the transmembrane dimer of amyloid precursor protein, [195] transmembrane structures of amyloid oligomers, [196] dimerization of the lutropin receptor, [197] gating of MscL, [198] the translocon, [199] peptide translocation through bilayers, [200] and others.…”
Section: Heterogeneous Solventsmentioning
confidence: 99%